1994
DOI: 10.1086/187641
|View full text |Cite
|
Sign up to set email alerts
|

ASCA solid state imaging spectrometer observations of O stars

Abstract: We report ASCA Solid State Imaging Spectrometer (SIS) X-ray observations of the O stars 60ri and 2 Ori. The energy resolution of the SIS allows us to resolve features iv. the O star X-ray spectra which are not apparent in spectra obtained by X-ray spectrometers with lower energy resolution. SIS spectra from both stars show evidence of line emission, suggesting the thermal nature of the X-ray source. However, the observed line strengths are different for the two stars. The observed stellar X-ray spectra are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
27
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 3 publications
11
27
0
Order By: Relevance
“…Their uncertainties are supposed to have the same relative values as those for the emission measures because the luminosity is mostly determined by the emission measures in this temperature range, and therefore L X ∝ EM. The total luminosities (summed over the three temperature components) in other energy bands (0.5-4 keV, 0.1-2.4 keV, and 0.4-4 keV) for Einstein, ROSAT, ASCA given in the papers by Cassinelli & Swank (1983), Haberl &White (1993), andCorcoran et al (1994), respectively, do agree with our values when taking differences in interstellar absorption or distance into account. The abundances are relative to solar photospheric values (Lodders et al 2009).…”
Section: A 3-t Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…Their uncertainties are supposed to have the same relative values as those for the emission measures because the luminosity is mostly determined by the emission measures in this temperature range, and therefore L X ∝ EM. The total luminosities (summed over the three temperature components) in other energy bands (0.5-4 keV, 0.1-2.4 keV, and 0.4-4 keV) for Einstein, ROSAT, ASCA given in the papers by Cassinelli & Swank (1983), Haberl &White (1993), andCorcoran et al (1994), respectively, do agree with our values when taking differences in interstellar absorption or distance into account. The abundances are relative to solar photospheric values (Lodders et al 2009).…”
Section: A 3-t Modelsupporting
confidence: 88%
“…The spectrum of δ Ori was studied in X-rays with earlier satellites by Cassinelli & Swank (1983), Haberl & White (1993), and Corcoran et al (1994) and most recently at high resolution A&A 550, A55 (2013) References. (a) Van Leeuwen (2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ROSAT All-Sky Survey detected several X-ray sources identified with new T Tauri stars Neuhäuser et al 1995Neuhäuser et al , 1997Alcalá et al 1996;Magazzu et al 1997). The central hot star was observed with ASCA by Corcoran et al (1994) who found a hard spectrum with temperatures of 0.3 and 2.3 keV. Recently, Barrado et al (2011) has performed an XMM-Newton observation of two fields to the east and west of the cluster centre, partially overlapping our observation.…”
Section: Introductionsupporting
confidence: 68%
“…Unacceptable fits of HD 104237 and HD 200775 seem to be caused by small structures in the spectra, which might be unknown emission lines or absorptions. The best-fit temperature ranges between kT $ 1 5 keV, which is significantly higher than the X-ray temperature of MS OB stars (kT < 1 keV; e.g., Corcoran et al 1994). …”
Section: Spectramentioning
confidence: 87%